Diagnóstico del servicio al usuario que prestan los subcentros de salud de Calceta - Loor Zamora, Gema María (2015)
The present study aimed to diagnose the service provided by the health subcenters in Calceta, corresponding to the district address Nº 13D06. Samples of 79 and 78 patients from the San Bartolo and Inés Moreno Health Center were taken respectively. For the object of study a closed type survey evaluated ten indicators and a control question that analyzed the quality of service at a general level. Statistical processing was performed in Excel, with the results that there is a delay in opening hours, inadequate distribution of time causing delays for patients, incivility by some professionals, confusing information, no medical supervision, slowness in the process of management of complaints and claims, extended period of reference and return referral system programming. The involvement of these problems is low and this was checked with the question of control where users rated the quality of service as good, according to the answer giving by 75% of San Bartolo and 60% of Inés Moreno patients interviewed. However to counter the negative effects of the detected shortcomings are proposed and socialized with an improvement plan with legal actions and practices for execution in short and long term in order to guarantee citizens the access to an equitable, solidarity, equal, quality and warmth service; having as purpose the achievement of good living.